2017
DOI: 10.1212/cpj.0000000000000312
|View full text |Cite
|
Sign up to set email alerts
|

cEEG electrode-related pressure ulcers in acutely hospitalized patients

Abstract: Background: Pressure ulcers resulting from continuous EEG (cEEG) monitoring in hospitalized patients have gained attention as a preventable medical complication. We measured their incidence and risk factors. Methods: We performed an observational investigation of cEEG-electrode-related pressure ulcers (EERPU) among acutely ill patients over a 22-month period. Variables analyzed included age, sex, monitoring duration, hospital location, application methods, vasopressor usage, nutritional status, skin allergies,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…These results are similar to other published studies that targeted EERPI prevention as their main outcome 20 . However, because most of the published data targeted adult populations, with only a handful of studies including neonates, this study furthers the QI methodology work for EERPI in this high-risk, understudied population 21,22 …”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These results are similar to other published studies that targeted EERPI prevention as their main outcome 20 . However, because most of the published data targeted adult populations, with only a handful of studies including neonates, this study furthers the QI methodology work for EERPI in this high-risk, understudied population 21,22 …”
Section: Discussionsupporting
confidence: 88%
“…20 However, because most of the published data targeted adult populations, with only a handful of studies including neonates, this study furthers the QI methodology work for EERPI in this high-risk, understudied population. 21,22 Risk factors for HAPI development include exposure to various diagnostic and therapeutic medical devices, inactivity or immobility, friction and shear, hypoxia and poor skin perfusion, fluid retention, and nutrition deficiencies; critically ill neonates may be exposed to all of these factors. 23,24 Visscher and Taylor 25 found a 6.4% rate of medical device-related PIs in neonates.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several studies highlighted a less serious safety issue of prolonged EEG monitoring; skin irritation or injuries at the EEG electrode sites are reported to occur in almost 8% up to 27% of patients, depending on the duration of the monitoring period [ 34 ]. Furthermore, the study conducted by Ouchida and colleagues in 2019 indicated a much higher prevalence, as most participants (82%) had skin irritation or injury at the electrode sites [ 35 ].…”
Section: Reviewmentioning
confidence: 99%
“…A limited array may also be used when a patient is anticipated to need cEEG monitoring for several days to reduce the number of sites at risk of skin breakdown. Risk factors for electrode-related skin injury include critical illness, longer duration of monitoring, age less than 1 year, fever, lack of headwrap, and need for vasoactive support [10][11][12]. The skin should be checked daily, and scalp rest should be provided if breakdown is identified.…”
Section: Technical Aspects Of Ceeg Monitoringmentioning
confidence: 99%